Long-range projection neurons of the mouse ventral tegmental area: a single-cell axon tracing analysis - Aransay, Ana; Rodríguez-López, Claudia; García-Amado, María; Clascá, Francisco; Prensa, Lucía (Frontiers in Neuroanatomy, 2015)
Pathways arising from the ventral tegmental area (VTA) release dopamine and other neurotransmitters during the expectation and achievement of reward, and are regarded as central links of the brain networks that create drive, pleasure, and addiction. While the global pattern of VTA projections is well-known, the actual axonal wiring of individual VTA neurons had never been investigated. Here, we labeled and analyzed the axons of 30 VTA single neurons by means of single-cell transfection with the Sindbis-pal-eGFP vector in mice. These observations were complemented with those obtained by labeling the axons of small populations of VTA cells with iotophoretic microdeposits of biotinylated dextran amine. In the single-cell labeling experiments, each entire axonal tree was reconstructed from serial sections, the length of terminal axonal arbors was estimated by stereology, and the dopaminergic phenotype was tested by double-labeling for tyrosine hydroxylase immunofluorescence. We observed two main, markedly different VTA cell morphologies: neurons with a single main axon targeting only forebrain structures (FPN cells), and neurons with multibranched axons targeting both the forebrain and the brainstem (F+BSPN cells). Dopaminergic phenotype was observed in FPN cells. Moreover, four “subtypes” could be distinguished among the FPN cells based on their projection targets: 1) “Mesocorticolimbic” FPN projecting to both neocortex and basal forebrain; 2) “Mesocortical” FPN innervating the neocortex almost exclusively; 3) “Mesolimbic” FPN projecting to the basal forebrain, accumbens and caudateputamen; and 4) “Mesostriatal” FPN targeting only the caudateputamen. While the F+BSPN cells were scattered within VTA, the mesolimbic neurons were abundant in the paranigral nucleus. The observed diversity in wiring architectures is consistent with the notion that different VTA cell subpopulations modulate the activity of specific sets of prosencephalic and brainstem structures.